Theoretical Analysis of Student Development Through Cognitive, Affective, and Psychomotor Approaches - Trisnawaty; Damopolii, Muljono; Yuspiani (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2025)
This study aims to examine strategies for holistic student development based on their individual characteristics. The method used is literature review with a conceptual-critical approach. The findings reveal that the development of students’ cognitive, affective, and psychomotor domains must be grounded in a thorough analysis of age, learning styles, cultural background, socioeconomic status, and special needs. Integration of these three domains is effectively achieved through contextual, differentiated, and inclusive teaching approaches such as Problem-Based Learning and Project-Based Learning. Learning tailored to students’ characteristics has been shown to enhance effectiveness, active participation, and the balance between academic achievement and character formation. This aligns with Islamic educational principles that emphasize the harmony of intellect (‘aql), heart (qalb), and body (jasad). Keywords: affective, cognitive, holistic, psychomotor, student characteristics